Budaya Pandalungan Sebagai Media Pendidikan Egaliter - Bambang Subahri; Ahmad Arif Ulin Nuha (Bidayatuna, 2022)
Pandalungan culture is a hybrid culture between Java and Madura with various traditions. Pandalungan culture is a miniature of a humanist egalitarianism learning system that can improve cognitive, affective, and pedagogical abilities without losing certain authorities. This research is qualitative field research that is ethnographic studies. The findings are as follows: 1. Egalitarian education is a conceptual framework, implementation, and implication of relevant learning to improve the quality of education 2. Pendalungan culture, with many traditions ranging from religious traditions to performing arts and many other traditions, teaches many things about treating society relatively 3. Egalitarian education is very decisive in students' behavior, as included in the psychology of child development to parenting which states that equality and respect for a person have a significant effect on learning.